Геополітична регіоналізація просторового розвитку України: методологічні стратегії - Литвин, В.М.; Верменич, Я.В. (Вісник НАН України, 2022)
У статті висвітлено стратегії застосування міждисциплінарних підходів до аналізу процесів геополітичної регіоналізації просторового розвитку України та впливу глобалізації на зміну сутності концептів простору
і території. Наголошено, що в умовах сучасних геополітичних реалій та
загострення конфліктності зосередження дослідницької уваги на тенденціях просторового розвитку України дасть змогу проаналізувати явища
регіональної асиметрії, запропонувати шляхи мінімізації дисбалансів, які
виникають на цьому ґрунті, та виробити алгоритми посилення консолідації суспільства. Показано, що геополітичні стратегії є не лише концептуальним орієнтиром, а й методологічним інструментарієм для осмислення
минулих та вибудови сучасних моделей просторового розвитку України, а
тому проблеми геополітичної регіоналізації простору і територіальних
трансформацій мають постійно перебувати як у фокусі регіональної аналітики держави, так і в епіцентрі національних стратегічних завдань та пріоритетних напрямів розвитку науки і техніки в Україні. The article highlights the strategies of applying interdisciplinary approaches to the analysis of the processes of geopolitical
regionalization of spatial development of Ukraine and the impact of globalization on changes in the essence of the
concepts of space and territory. Geopolitical and geocultural concepts are considered in the context of forming the theoretical
foundations of geostrategic thinking and representation of space as a socio-cultural integrity with its own territorial
identity. It is emphasized that in the current geopolitical realities marked by conflict escalation, focusing on research
trends in Ukraine’s spatial development will identify regional asymmetries, suggest ways to minimize the imbalances that
arise on this basis and present algorithms to strengthen the consolidation of society. It is shown that the contradiction of
global, national and regional interests in Ukrainian socio-cultural space is largely due to geopolitical differences inherited
from previous state organisms. Historical reconstruction of spatial networks serves to compare cycles and motives of
socio-cultural development of territories, conduct the analysis of modernization and urbanization processes, origins and
consequences of spatial conflicts, directions and rates of socio-political transformations. It is proved that geopolitical
strategies are used not only as a conceptual guideline, but also as a methodological tool for understanding the past and
building modern models of spatial development of Ukraine. This means that the problems of geopolitical regionalization
of space and territorial transformations must constantly remain not only in the focus of regional analysis of the state, but
also at the epicenter of national strategic objectives and priorities for science and technology in Ukraine.